Lightning related fish mortality: case study from Bangladesh - Gomes, Chandima; Ahmed, Munir; Zele, Diana (IEEE, 2012)

(untitled)
This paper reports and analyses somewhat rare observation related to lightning. In several occasions a large number of Climbing Perch or Koi fish (Anabas testudineus) were reported dead after ground lightning events, in set of commercial fish ponds in Bangladesh. In ponds where several other fish varieties are farmed, only Koi fish is affected. The farmers and neighbourhood attributes the deaths to the erection of a mobile communication tower in the proximity, as the number of affected fish increases as one moves towards the ponds adjoin the tower. Site visits and interviews revealed various facts related to the incident. We show that nearby lightning to a structure having large ground resistance may lead to surface current that provide sufficient lethal energy to kill a fish that swims in surface water.